Surgical technique and comparison of autologous cancellous bone grafts from various donor sites in rats. Issue 4 (27th August 2022) - Gens, Lena; Marchionatti, Emma; Steiner, Adrian; Stoddart, Martin J.; Thompson, Keith; Mys, Karen; Zeiter, Stephan; Constant, Caroline
Abstract: Autologous cancellous bone graft is the gold standard in large bone defect repair. However, studies using autologous bone grafting in rats are rare. To determine the feasibility of autologous cancellous bone graft harvest from different anatomical donor sites (humerus, ilium, femur, tibia, and tail vertebrae) in rats and compare their suitability as donor sites, a total of 13 freshly euthanized rats were used to describe the surgical technique, determine the cancellous bone volume and microstructure, and compare the cancellous bone collected quantitatively and qualitatively. It was feasible to harvest cancellous bone grafts from all five anatomical sites with the humerus and tail being more surgically challenging. The microstructural analysis using micro‐computed tomography showed a significantly lower bone volume fraction, bone mineral density, and trabecular thickness of the humerus and iliac crest compared to the femur, tibia, and tail vertebrae. The harvested weight and volume did not differ between the donor sites. All donor sites apart from the femur yielded primary osteogenic cells confirmed by the presence of alkaline phosphatase and Alizarin Red S stain. Bone samples from the iliac crest showed the most consistent outgrowth of osteoprogenitor cells. In conclusion, the tibia and iliac crest may be the most favorable donor sites considering the surgical approach. However, due to the differences in microstructure of the cancellous bone and the consistency of outgrowth of osteoprogenitor cells, the donor sites may have different healing properties, that need further investigation in an in vivo study.